(untitled) (Computer systems and information technologies, 2025)
Nowadays, the era of waiting in lines, writing official letters, and direct contact with employees of institutions, establishments, and companies is gradually becoming a thing of the past. Instead, the problem of creating tools that ensure the development, implementation, and implementation of chatbots and agents, their support, and expansion of functionality, and scalability, arises. The main subject of this article is precisely the representation of a chatbot in the form of a state diagram. This technology, together with the technology of analysis and synthesis of formal chatbot models, constitute important components of the platform and information systems as a whole for institutions, establishments, and companies of various levels. An analysis of the possibilities of automata theory has shown the feasibility of using transitional systems and finite automata such as X-automata, Mealy and Moore automata as chatbot models. The article describes a general approach to the effective representation of a chatbot in the form of a state diagram, implemented within the framework of a platform for the development, accumulation, and use of chatbots. As a formal model of a chatbot, it is proposed to use finite automata of Mealy and Moore, and the transformation of a regular expression, which is based on the input and output alphabets of the system, to a certain graphic configuration is proposed to be carried out according to the algorithm presented in [11]. In the case of a formal description of the business process, the corresponding transition system or automaton is formed on the basis of a decision tree containing pairs <initial state, final state>. If there is no description of the business process, then an algorithm for synthesizing the corresponding automaton based on a set of necessary lines of behavior/scenarios represented by regular expressions is proposed. Based on the synthesis, a ready-made solution for a telegram bot was formed, on the basis of which a telegram bot was created using the existing messenger software interface and the execution time of a particular line of behavior/scenario for a specific task "Taxi Ordering". Taking into account the time and sequence of message and response creation, an approach was also proposed to calculate the chatbot operation time for different scenarios. It was determined that for standard scenarios T1= 204 (s), T2=324 (s), T3=467 (s), T4=80 (s) provided that the response from the data source (web service) on the available car types and the actual availability of the selected car is received in less than 20 seconds.